Livestock Waste-to-Bioenergy Generation Potential in Uganda: A Review - Prosper Achaw, Owusu (Environmental Research, Engineering and Management, 2017)
Livestock waste-to-energy (WTE) is a unique type of energy source which can be tapped to supplement current energy need and also help improve the current waste management problems existing in most parts of the world. This review paper sought to assess the potential of Uganda to convert the waste from its rich livestock production to supplement its energy demand. The amount of bioenergy potential was estimated from a number of cattle, sheep, goat, pig and poultry based on descriptive statistics data. Other feedstock sources for biogas generation were also identified. It was estimated that Uganda has the potential to produce 1258.37 million m3 of biogas annually which is equivalent to 25.17 PJ of energy from cattle, goat, pig, sheep and poultry wastes when treated anaerobically. The potential biogas generation in Uganda was estimated as 888.21, 55.83, 191.00, 85.82 and 37.51 million m3 y-1 for cattle, sheep, goat, pig and poultry respectively. The Government of Uganda have set a target of installing about 100,000 biogas digesters by the year 2017, only 50% of about 500 installed digesters are in operation. It was recommended that the Government of Uganda should make biogas production a priority since it can supplement the Rural Electrification Programme.
Keywords: Bioenergy, biogas, waste management, renewable energy, Uganda